2020
DOI: 10.1080/03007995.2020.1754182
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and effectiveness of biosimilar insulin glargine in Japanese patients with diabetes mellitus in routine clinical practice: results of a post-marketing safety study

Abstract: Objective: To evaluate the long-term safety and effectiveness of biosimilar insulin glargine (GLY) in real-world clinical practice. Methods: This prospective, non-interventional, multicenter, observational, post-marketing safety study (PMSS) enrolled Japanese patients with type 1 or 2 diabetes mellitus (T1DM or T2DM) starting GLY therapy, and was required by Japanese Pharmaceutical Affairs Law mandating post-marketing safety surveillance to acquire safety and effectiveness data of biosimilar products. Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Follow-on biologics cannot be substituted for the originator without a new prescription. Similar to our results, the real-world studies comparing the follow-on biologic with the originator found no significant differences in effectiveness and safety [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…Follow-on biologics cannot be substituted for the originator without a new prescription. Similar to our results, the real-world studies comparing the follow-on biologic with the originator found no significant differences in effectiveness and safety [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…A limited number of post-marketing clinical studies and limited real-world data are available. The current data suggest that the biosimilars and their RBP have comparable safety and efficacy profiles [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each participating country locally ensured that all necessary regulatory submissions were performed in accordance with local regulations including local data protection regulations. The Institutional Review Board of King Abdulaziz University in Saudi Arabia (Reference number [17][18] has approved this study. All patients signed an informed consent form before any study-related activity.…”
Section: Methodsmentioning
confidence: 99%